A novel 2.6–6.4 GHz highly integrated broadband GaN power amplifier - Liu, Bei (2019)
In this letter, a novel methodology to achieve output broadband matching is proposed. Based on this methodology, a broadband gallium nitride power amplifier (PA) with input matching and stabilization circuit integrated on-chip is designed. The implemented PA achieves a maximum drain efficiency of 62%-79.2% from 2.6 to 6.4 GHz (84.4% fractional bandwidth), with a saturated output power (Psat) of 34.3-35.8 dBm, while providing a gain larger than 10 dB. When tested with 802.11ac VHT80 MC9 (80 MHz, 256-QAM) with 11.3-dB peak-to-average power ratio, PA achieves a drain efficiency of 22.1%-25.2% with an average output power of 23-25.4 dBm across the whole band, while meeting the standard specification of error vector magnitude below -32 dB.